2012
DOI: 10.1111/j.1365-2567.2012.03598.x
|View full text |Cite
|
Sign up to set email alerts
|

Haem oxygenase 1 expression is altered in monocytes from patients with systemic lupus erythematosus

Abstract: 1 expression was measured by RT-PCR. In addition, HO-1 protein expression was determined by FACS. HO-1 levels in monocytes were significantly reduced in patients with SLE compared with healthy controls. These results were confirmed by flow cytometry. No differences were observed in other cell types, such as DCs or CD4 + T cells, although decreased MHC-II levels were observed in DCs from patients with SLE. In conclusion, we found a significant decrease in HO-1 expression, specifically in monocytes from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 58 publications
(103 reference statements)
3
29
0
Order By: Relevance
“…Splenocytes from HO‐1 KO mice also showed an augmented secretion of pro‐inflammatory cytokines, such as interleukin‐1 (IL‐1), IL‐6 and tumour necrosis factor‐ α . Consistent with these observations, monocytes from patients suffering from the autoimmune disease systemic lupus erythematosus, which manifests as exacerbated general inflammation, showed a reduced expression of HO‐1 . Similar results were seen in patients with multiple sclerosis, who displayed reduced levels of HO‐1 in peripheral blood mononuclear cells during disease exacerbation .…”
Section: Biological Function Of Ho‐1 Activitysupporting
confidence: 78%
“…Splenocytes from HO‐1 KO mice also showed an augmented secretion of pro‐inflammatory cytokines, such as interleukin‐1 (IL‐1), IL‐6 and tumour necrosis factor‐ α . Consistent with these observations, monocytes from patients suffering from the autoimmune disease systemic lupus erythematosus, which manifests as exacerbated general inflammation, showed a reduced expression of HO‐1 . Similar results were seen in patients with multiple sclerosis, who displayed reduced levels of HO‐1 in peripheral blood mononuclear cells during disease exacerbation .…”
Section: Biological Function Of Ho‐1 Activitysupporting
confidence: 78%
“…These observations suggest that it is probably the reduction of immunogenic signals, instead of the up‐regulation of suppressive molecules, that is the key to achieving a tolerogenic DC phenotype. Although monocytes from patients with SLE have abnormal properties, our results suggest that functional tolDCs can be obtained from them and autologous immunotherapy for SLE may in fact be plausible, even with the described particular characteristics of this cell type in patients with SLE …”
Section: Discussionmentioning
confidence: 78%
“…In addition to the increased expression of co‐stimulatory molecules, myeloid cells from SLE patients show reduced expression of the anti‐inflammatory enzyme HO‐1 . Here, we evaluate whether HO‐1 induction in combination with Dexa and Rgz generates an improved tolerogenic profile.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that treatment with Dexa blocks DC maturation and it has been previously used together with Rgz, which is a known nuclear factor‐ κ B inhibitor . HO‐1 is a critical enzyme involved in renal protection and its expression is reduced in SLE patients . Induction of this enzyme has been related to amelioration in lupus‐prone mice .…”
Section: Discussionmentioning
confidence: 99%